Analysis of 4C’s-Based Lesson planning in the Islamic Religious Education Study Program - Karolina, Asri; Destriani, Destriani; Warsah, Idi; Astuti, Mardiah; Yunierti Prihatin, Nyimas (Corolla International Conference, 2024)
This study aims to analyze the 4C's-based learning planning in the Islamic Religious Education Study Program at the Faculty of Tarbiyah. Previous research has shown that the application of the 4C learning strategies (Creative Thinking, Critical Thinking and Problem Solving, Communication, Collaboration) in Islamic Religious Education can enhance students' skills. This research can contribute to the development of more effective and innovative learning strategies in the Islamic Religious Education Study Program at the Faculty of Tarbiyah. The study employs a descriptive qualitative approach, with the subjects being the Head of the PAI Study Program, PAI lecturers, and students, using purposive sampling. The primary data include lecturers and students, while the primary sources consist of lecturer lesson plans, books, and journals. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data condensation, data presentation, and data verification, with data reliability tested through source and technique triangulation. The study shows that PAI lecturers at the Faculty of Tarbiyah implement strategies and teaching methods that support the development of the four aspects, such as collaborative learning, discussions, Q&A, research-based learning, material reviews, presentations, assignments, quizzes, active learning, and TPACK-based projects using QR codes, Mind Master, Canva, and Kahoot. It is concluded that the Faculty of Tarbiyah has made efforts to develop 4C's skills in students of the Islamic Religious Education Study Program by designing appropriate learning plans and integrating various effective learning models and strategies.